(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Security and energy efficiency is of paramount importance in a wireless sensor network. This is due to their vulnerable deployment conditions and battery based power. This paper presents a secure and distributed algorithm that generates routes on-demand in a wireless sensor network. Dynamic route generation is facilitated by PSO, a metaheuristic technique. Current network traffic in that route and charge contained in the candidate node are used as evaluation parameters along with the node distance, hence a huge reduction in the packet loss was observed. Experiments were conducted and it was observed that the proposed algorithm exhibits very low selection overhead and also provides distributed routs, which eventually lead to prolonged network lifetime.